Bulk liquid pertraction of NaCl from aqueous solution using carrier-mediated transport. Issue 4 (16th February 2016) - Naim, M.M.; El-Shafei, A.A.; Moneer, A.A.; Elewa, M.M.; Kandeel, W.G.
Abstract : In the present work, removal of NaCl using the bulk liquid membrane (BLM) technique has been investigated, using a simple apparatus for conducting the experiments. Variables investigated were volume ratio of donor phase (DP) to receptor phase (RP), presence of sequestering agent (SA) in RP, type of organic liquid membrane (LM), quantity of mobile carrier (MC) in the LM. Stirring speed and volume of LM were kept constant at 100 rpm and 130 ml, respectively. The mass transfer of NaCl was analysed based on kinetic laws of two consecutive irreversible first-order reactions, and kinetic parameters ( k 1 d, k 2 m, k 2 r, , t max, , and ) for the transport of NaCl were investigated. The values obtained demonstrate that the process is diffusionally controlled. Results indicate that the membrane entrance and exit rate constants ( k 1, k 2 ) increase with decreasing DP:RP ratio and with decrease in quantity of MC, and quantity of SA, and the presence of dichloroethane (DCE) is preferred to chloroform (CF) as LM.